Analysis of Efficiency of Use of the Longitudinal-Flow Hydropower Plant Unit of a Micro Hydropower Station without a Dam for Small Rivers - KRASNOV, Victor G.; OBOZOV, Alaibek D.; NURISLAMOV, Oleg R. (Journal of Environmental Management and Tourism, 2018)
In the research of alternative sources of energy much attention is paid to hydro energy, in particular, micro hydropower stations, which use rivers’ kinetic energy. This issue is relevant for research. The target of this paper is to analyze the efficiency of longitudinal-flow hydropower plant of a micro hydropower station without a dam for small rivers. The operational efficiency of hydraulic power plants is mainly determined by the interaction of working elements with the hydraulic flow and the utilization level of its characteristics. The features of its usage and the influence of flow characteristics of the hydropower stations efficiency are examined in this paper. Besides, the interaction between the flow and working elements is assessed. The possibility of improving efficiency level by using working elements with changing weight is tested. Moreover, empirical data is used for calculations.